2017
DOI: 10.1104/pp.16.01698
|View full text |Cite
|
Sign up to set email alerts
|

Root Cell-Specific Regulators of Phosphate-Dependent Growth

Abstract: Cellular specialization in abiotic stress responses is an important regulatory feature driving plant acclimation. Our in silico approach of iterative coexpression, interaction, and enrichment analyses predicted root cell-specific regulators of phosphate starvation response networks in Arabidopsis (Arabidopsis thaliana). This included three uncharacterized genes termed Phosphate starvation-induced gene interacting Root Cell Enriched (PRCE1, PRCE2, and PRCE3). Root cell-specific enrichment of 12 candidates was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 132 publications
1
15
0
Order By: Relevance
“…By contrast, other CIPK genes were abundantly expressed in certain tissues. For example, ScCIPK4 was mainly expressed in roots, as also reported Linn et al (2017) in Arabidopsis whereas the expression of ScCIPK25 was detected in flowers and roots, consistent with data by Meena et al (2018).…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, other CIPK genes were abundantly expressed in certain tissues. For example, ScCIPK4 was mainly expressed in roots, as also reported Linn et al (2017) in Arabidopsis whereas the expression of ScCIPK25 was detected in flowers and roots, consistent with data by Meena et al (2018).…”
Section: Discussionsupporting
confidence: 91%
“…Compared with the wild type, all mutant lines tested displayed lower shoot biomass under optimal growth conditions ( Fig. 4B, P-replete), asserting that the maintenance of P i homeostasis is linked to plant fitness (Rouached et al, 2011;Linn et al, 2017). Mutants were not impaired in root growth (Fig.…”
Section: Disruption Of Spx4 Function Leads To P I Overaccumulation Inmentioning
confidence: 82%
“…4; Supplemental Fig. S7D; Aung et al, 2006;Bari et al, 2006;Linn et al, 2017). Common effects on PSR gene expression are still unexpected, given that PHO2 function in roots has been primarily associated with controlling trafficking of PHT1;1/4 transporters and PHO1 exporter from the endoplasmic reticulum to the plasma membrane via its ubiquitin E2 conjugase activity Figure 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pi deficiency response is orchestrated by intricate signaling networks, involving hormones, nutrient cross talk, and transcriptional and translational feedback loops (for review, see Abel, 2017;Chien et al, 2018). Ca 2+ has been hypothesized to be involved as a signal transducer (Chiou and Lin, 2011;Linn et al, 2017;Chien et al, 2018), but this has not been confirmed to date.…”
mentioning
confidence: 99%